2019
DOI: 10.1021/acsami.9b00606
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Chemistry in Mediating the Uptake of Ultrasmall Iron Oxide Nanoparticles by Cancer Cells

Abstract: Ultrasmall iron oxide nanoparticles (USIONPs) (<4 nm) have recently attracted significant attention because of their potential as positive T 1 magnetic resonance imaging (MRI) contrast agent contrary to larger superparamagnetic iron oxide nanoparticles (>6 nm) which act as negative T 2 MRI contrast agents. However, studies on the cellular uptake behavior of these nanoparticles are very limited compared to their counterpart, larger-sized superparamagnetic iron oxide nanoparticles. In particular, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The result revealed that these cancer cells selectively uptaked QA-USION, which was partially mediated by p-selectin. 75…”
Section: Dovepressmentioning
confidence: 99%
“…The result revealed that these cancer cells selectively uptaked QA-USION, which was partially mediated by p-selectin. 75…”
Section: Dovepressmentioning
confidence: 99%
“…Recently, ultrasmall iron oxide nanoparticles (USIONPs) of size <4 nm were used as a positive T1 relaxivity MRI contrast agent, as they offer bright MRI imaging and high-resolution, resulting in easy detection of the target (Liu et al, 2019). Recently, Rao et al reported the synthesis of quinic acid (QA)-coated USIONPs to target P-selectin overexpressed aggressive cancer cells (Narkhede et al, 2019).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Recently, ultrasmall iron oxide nanoparticles (USIONPs) of size <4 nm were used as a positive T1 relaxivity MRI contrast agent, as they offer bright MRI imaging and high-resolution, resulting in easy detection of the target ( Liu et al, 2019 ). Recently, Rao et al reported the synthesis of quinic acid (QA)-coated USIONPs to target P-selectin overexpressed aggressive cancer cells ( Narkhede et al, 2019 ). Working under the same notion, Liu et al reported the synthesis of USIONPs-PEG-SLex nanoparticles to assess in vivo E-selectin expression level in nasopharyngeal carcinoma (NPC) metastasis ( Liu et al, 2019 ).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Intensive efforts have been made to improve the analytical performance of conventional MNP-implemented MRS sensors. We and other researchers have used different strategies to improve the sensitivity and stability of conventional MRS biosensors, but they are still not competent to detect small molecules with facile operation. ,, Alternatively, we have resorted to paramagnetic ion-mediated MRS sensors where the valence state change of paramagnetic ions such as Fe 3+ and Cu 2+ can result in a significant change in the T 1 / T 2 signal of NMR. , For example, we have reported the difference in T 1 values of water protons between Fe 2+ and Fe 3+ aqueous solutions and developed a range of assays using their interconversion. Compared with MNPs, the use of paramagnetic ions have two advantages: (i) It is much easier to prepare the aqueous solution of paramagnetic ions than that of MNPs and the paramagnetic ion solution generally has a longer shelf life and (ii) paramagnetic ions have different valence states that can be interconverted by redox reactions, providing a versatile magnetic sensing platform.…”
Section: Introductionmentioning
confidence: 99%
“…We and other researchers have used different strategies to improve the sensitivity and stability of conventional MRS biosensors, but they are still not competent to detect small molecules with facile operation. 13,17,18 Alternatively, we have resorted to paramagnetic ion-mediated MRS sensors where the valence state change of paramagnetic ions such as Fe 3+ and Cu 2+ can result in a significant change in the T 1 /T 2 signal of NMR. 19,20 For example, we have reported the difference in T 1 values of water protons between Fe 2+ and Fe 3+ aqueous solutions and developed a range of assays using their interconversion.…”
Section: ■ Introductionmentioning
confidence: 99%